INTEGRATED ANTENATAL CARE BY MIDWIVES IN SURABAYA - Dian Lestari; Gadis Meinar Sari (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: The maternal mortality rate in Indonesia is still high and still far from the established target of SDG's, which is 307 maternal deaths per 100,000 live births. Adequate antenatal cares are needed to reduce maternal mortality. This study aims to determine the quality of antenatal care (ANC) services at public health centers by the framework of systems (Input, process, and output). Methods:  This study is a descriptive study with qualitative designs. Data collection was conducted in 12 health centers and the sample size is 12 midwives in the health centers. Midwives were interviewed about input, process and output components related to integrated antenatal program (ANC Terpadu 10T). In addition, it was observed also the availability of facilities, infrastructure and K1 and K4 rate related to ANC in health centers. Results: Human resources in the implementation of the integrated antenatal program by midwives at the Surabaya's Health Center still do not meet the minimum health human resources standards. Public Health Centers observed have facilities and infrastructure to support integrated antenatal care.